Use of prophylactic pegfilgrastim for chemotherapy-induced neutropenia in the US: A review of adherence to present guidelines for usage. (2021) - Crawford, Jeffrey; Moore, Donald C.; Morrison, Vicki A.; Dale, David
Highlights: Real-world data reveal widespread deviation from US guidelines on pegfilgrastim use. Potential pegfilgrastim under-use in patients at high risk of FN has been observed. Over-use is common in those at low risk of FN or receiving palliative chemotherapy. Guideline deviation is responsible for a large proportion of FN hospitalizations. Claims analyses report increased risk of FN in cycle 1 with same-day pegfilgrastim. Abstract: Evidence-based US guidelines provide recommendations for the use of granulocyte colony-stimulating factor (G-CSF) as supportive therapy in patients with cancer receiving chemotherapy. Pegfilgrastim is recommended for FN prophylaxis in patients with non-myeloid malignancies receiving a high-risk chemotherapy regimen, or an intermediate-risk regimen if one or more risk factors are present. The guidelines highlight the patient characteristics and chemotherapy regimens for solid tumors and hematologic malignancies that may influence a patient's overall risk of FN and may benefit from pegfilgrastim support. This review aimed to evaluate how pegfilgrastim use in patients with cancer receiving myelosuppressive chemotherapy in routine clinical practice aligns with evidence-based US guidelines. Examination of the literature revealed widespread deviation in relation to under- and over-prescribing, and timing of administration in US clinical practice. Pegfilgrastim is often over-prescribed in patients receiving palliative chemotherapy and those at low risk of FN. Potential under-prescribing of pegfilgrastim was also observed. In this literature search, data that appear to support same-day administration of pegfilgrastim were from uncontrolled studies that were limited in size. Analyses of healthcare claims data clearly favored next-day use, with statistically significant increases in FN incidence among patients receiving same-day pegfilgrastim versus those treated 1–4 days post-chemotherapy. Earlier-than-recommended administration typically occurs at the physician's discretion where next-day administration might present barriers to the patient receiving supportive therapy.There is a need to ensure appropriate prescribing to optimize patient outcomes, as deviation from the guideline recommendations was associated with increased incidence of FN and hospitalization. Graphical abstract: Image, graphical abstract